1998
DOI: 10.1002/(sici)1097-0231(19980715)12:13<837::aid-rcm248>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Asp-Pro bond under high and low energy collision induced dissociation conditions in the immunodominant epitope region of Herpes simplex virion glycoprotein D

Abstract: A series of truncated Herpes simplex virion peptides studied by fast atom bombardment mass spectrometry under high and low energy collision induced dissociation conditions showed preferential fragmentation of the aspartyl-proline amide bond, compared to other peptide bonds. Electrospray ionization investigation proved that this favoured fragmentation can not be attributed to only the known proline effect, as a change from Asp to Asn in the peptide yielded an Asn-Pro bond which was found to be stable under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Dramatic differences are evident from the distribution of product ions. In the positive ion mode, the intense cleavage products can be rationalized by postulating an initial fragmentation at the X-Pro bond [4,19,21,22]. In the positive ion mode, the single intense peak at m/z 959 corresponds to loss of NH 3 from the C-terminal primary amide group.…”
Section: Contryphanmentioning
confidence: 99%
“…Dramatic differences are evident from the distribution of product ions. In the positive ion mode, the intense cleavage products can be rationalized by postulating an initial fragmentation at the X-Pro bond [4,19,21,22]. In the positive ion mode, the single intense peak at m/z 959 corresponds to loss of NH 3 from the C-terminal primary amide group.…”
Section: Contryphanmentioning
confidence: 99%
“…The crude product of peptide 270-284 contained approximately 25% byproducts as a result of splitting the Asp-Pro bonds after cleavage from the resin with hydrogen fluoride (HF) and in the following work-up procedure in acetic acid solution [11][12][13]. The fast atom bombardment collision induced dissociation (FAB-CID) study of the same set of peptides showed that neither the length nor the amino acid composition of the peptide had a significant influence on this preferential cleavage [14]. At the same time we observed different stability of the closely related NP and DP bonds.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time we observed different stability of the closely related NP and DP bonds. Mák et al suggested that the analysis of the mass spectrometric fragmentation behaviour of the peptides might provide useful information for understanding the chemical sensitivity of Asp-Pro peptide bonds [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Ac‐IPG tag is based on selective N‐terminal dimethylation (Koehler et al, 2013 ; Qin et al, 2012 ) followed by derivatization of the epsilon‐amine group at the C‐terminal Lys residue of LysC peptides with isobaric Ac‐IPG tags having complementary isotope distributions on Pro‐Gly and Ac‐Ile, as shown in Figure 17B . Fragmentation occurs between Ile and Pro (Dongre et al, 1996 ; Hogan & McLuckey, 2003 ; Huang et al, 2004 ; Mák et al, 1998 ; Tiwary et al, 2019 ) in addition to fragmentation of the peptide backbone upon CID. While the resulting y‐ions can be distinguished between labeling channels based on the distinct isotopes on the Pro‐Gly part and thus contain the quantitative information for the respective peptides, b‐ions of the different labeling channels have identical m/z values, which allows database searching with commonly used algorithms (see Figure 17C ).…”
Section: Ms2‐based Quantificationmentioning
confidence: 99%